KONSEP KEMISKINAN DAN PENDEKATAN PENGENTASANNYA - Nandang Najmulmunir (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2003)
The Development have impacted a poverty. There are many concepts of poverty and its alleviation. The poverty concept can be seen in the type of absolute, natural and relative one: There are many approach to measure the poverty condition and there are many ways to alleviate them.